Connectivity between populations of the scallop Pecten maximus in the Irish Sea and the implications for fisheries management - Close, Hayden; Lambert, Gwladys; Robins, Peter; Gimenez, Luis (Frontiers in Marine Science, 2024)
Marine species with a pelagic larval phase have the potential to disperse hundreds of kilometres via ocean currents, thus connecting geographically distinct populations. Connectivity between populations therefore plays a central role in population dynamics, genetic diversity and resilience to exploitation or decline and can be an important vector in the management of fisheries. The scallop, Pecten maximus, is a valuable benthic bivalve with a variety of management measures at both regional and national scales. A bio-physical numerical model was developed to simulate and characterise the larval transport and population connectivity of scallops across commercial fishing grounds within the Irish and Celtic Seas. The model incorporated realistic oceanographic currents and known behavioural traits of P. maximus larvae including spawning times, pelagic larval duration, and vertical migration during the various developmental stages i.e., passive, active swimming, vertical migrations, since growth rates change with temperature, which varies spatially and temporally, it was used in the model to determine when an individual larva changed its behaviour. Simulations showed a high degree of connectivity between most populations, with multiple connections allowing for substantial exchanges of larvae. The exception was a population off North Cornwall that was entirely reliant on self-recruitment. A sensitivity analysis of the biological parameters suggested that ocean current patterns primarily controlled the connectivity network, but the strength of the connections was sensitive to spawning date and the specific features of diel vertical migrations. The model identified weakly connected populations that could be vulnerable to overfishing, and populations that are ‘strong connectors’ and a vital source of larvae to maintain the metapopulation. Our approach highlights the benefits of characterising population connectivity as part of an effective management strategy for sustainable fisheries.